An exceptional 5:4 enantiomeric structure. Issue 2 (1st April 2016) - Wachter, Erin; Glazer, Edith C.; Parkin, Sean; Brock, Carolyn Pratt
Abstract : The difficulty of obtaining crystals of a resolvable [Ru L 3 ] 2+ cation is consistent with the remarkably complex structure of its PF6 − salt. Abstract : The only crystals that could be grown from racemic solutions of the PF6 − salt of the resolvable cation [Ru(2, 9‐dimethyl‐1, 10‐phenanthroline)2 (dipyrido[3, 2‐ d :2′, 3′‐ f ]quinoxaline)] 2+ have translational symmetry only (space group P 1), contain nine independent sets of ions, and include numerous independent solvent molecules (11 acetone, one diethyl ether and possibly several water molecules). Layers of hydrophobic cations alternate with layers containing most of the anions and solvent molecules. All nine cations have the same basic conformation, which is distorted by the presence of the methyl substituents on the two 1, 10‐phenanthroline ligands. Four pairs of enantiomeric cations within a layer are related by approximate inversion centers; the ninth cation, which shows no sign of disorder, makes the layer chiral. Within the cation layers stripes parallel to [110] of six cations alternate with stripes of three; the local symmetry and the cation orientations are different in the two stripes. These stripes are reflected in the organization of the anion/solvent layer. The ca 80:20 inversion twinning found indicates that enantiomeric preference is transmitted less perfectly across the anion/solvent layer than within the cation layer. The structure is exceptional in having nine independent formula units and an unbalanced set (ratio 4:5) of resolvable enantiomers. The difficulty in growing crystals of this material is consistent with its structural complexity.